2002
DOI: 10.1210/jc.87.2.438
|View full text |Cite
|
Sign up to set email alerts
|

Dermopathy of Graves' Disease (Pretibial Myxedema): Long-Term Outcome

Abstract: Little is known about the long-term outcome of patients with thyroid dermopathy, an extrathyroidal manifestation of Graves' disease. Also, it is not known to what degree treatment promotes remission of the lesions. The present report supplies information on the natural course of mild, untreated and severe, treated thyroid dermopathy. In this study, we report on the outcomes of 178 patients seen at our institution between January 1969 and November 1995 with thyroid dermopathy who were followed up for an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 31 publications
0
91
1
1
Order By: Relevance
“…Women are more frequently affected than men, with female:male ratio of 3.5:1 [2]. It may present as various morphological variants, including nonpitting oedema (43.3%), plaque (27%), nodule (18.5%) and elephantiasis (2.8%) [3]. Though the pretibial area is the classical site of involvement in PM, rarely it has been reported to occur at unusual locations such as the forearms, shoulders, arms, palms, upper back, neck, pinnae and lower part of the abdomen [4].…”
Section: Discussionmentioning
confidence: 99%
“…Women are more frequently affected than men, with female:male ratio of 3.5:1 [2]. It may present as various morphological variants, including nonpitting oedema (43.3%), plaque (27%), nodule (18.5%) and elephantiasis (2.8%) [3]. Though the pretibial area is the classical site of involvement in PM, rarely it has been reported to occur at unusual locations such as the forearms, shoulders, arms, palms, upper back, neck, pinnae and lower part of the abdomen [4].…”
Section: Discussionmentioning
confidence: 99%
“…Претибиальная микседе-ма в большинстве случаев специального лечения не требует, иногда применяются кремы, содержащие кортикостероиды. Лечение тяжелой офтальмопатии при диффузном токсическом зобе системными кор-тикостероидами и октреотидом также эффективно воздействует на претибиальную микседему [29,30].…”
Section: дополнительные методы исследованияunclassified
“…Kriss et al (10) and Fatourechi et al (2,3) have reported moderate benefits of topical corticosteroid therapy. A long-term experience with thyroid dermopathy has been reported by only one group (2,3,13 A 53-year-old Japanese man visited our department with rapidly developing localized pretibial myxedema (PTM) and was admitted to our hospital (Fig. 1A, Fig.…”
Section: Localized Myxedema Is An Infrequent Manifestation Of Graves'mentioning
confidence: 99%